LANGUAGE ATTITUDE TOWARDS BLENDED LEARNING MODEL FOR WRITING SUBJECT - Wahyuni, Sri; Etfita, Fauzul (AL-ISHLAH: Jurnal Pendidikan, 2019)
The aim of this research is to analyze students? language attitude towards blended learning model for writing subject. The mix method was applied through the combination of quantitative data and qualitative data. The former was administered to the students through the four-point likert scale survey. The latter was obtained from the interview. The data was processed and computed by employing SPSS 24, then explained descriptively. The result of the study was classified into three categories namely affective, cognitive, and conative. The first was at moderate level with range 2.51--3.50. The second was at moderate level with range 2.51--3.50. The last was at moderate level with range 2.51--3.50. Overall, it is confirmed that the students positively behave on blended learning model in writing subject. In emphasizing the result, the interview illustrated that students showed good attitude on writing subject when taught by using blended learning model.